Military Orders’ role within the Portuguese medieval war recruitment - Costa,Paula Pinto (2020)
Abstract The war organization performed by the Portuguese Crown and by the Military Orders made themselves dependent on the recruitment of external people (namely from the aristocracy and from the municipal militias). Although the recruitment and the mobilization required to both some complex and joint procedures, we intend to understand if the Military Orders had assumed any independent role in this kind of missions. Thinking on these questions, we aim at contributing both to a deep knowledge of the Military Orders’ armies and to the relevance of their military groups within the royal armies in which they were involved.